Report of the High Level Group on Services Sector - Planning Commission (Planning Commission, 2008)
The Planning Commission had constituted a High Level Group on Services Sector on 4th May, 2007 under the chairmanship of Member (International Economics), Planning Commission for comprehensively examining the different aspects influencing the performance of the services sector and suggest short-term and long-term policy measures to improve and sustain its competitiveness in the coming years. A copy of the Order constituting the Group is given in Annexure I.
Government of India, Planning Commission